Modeling of differentiated physical fitness in school children - V.G. Arefiev (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: to develop a model of physical fitness training for schoolgirls to surrender standard- tives of physical culture (for example, high jump with a running start). Objectives of the study - to determine the relationship between the levels of development of motor skills and results in the high jump with a running start. Also calculate simple regression equation between them. Material : The study involved 416 school - prostrate aged 10-17. Results : It was found that the greatest influence on the effectiveness of the jump exerts a level of "explosive" force the leg muscles (30,4-47,9 %). The relative influence of mobility power 15,4-23,9 %. The share accounted speed 8,6-15,8 %. Impact indicators flexibility and endurance is 7,6-12,4 % and 4,4-7,2 %. Conclusions : The selection of exercises and methods advantageously carried out after comparing models of physical fitness and the actual state of development of motor characteristics. This makes it possible to determine the quantitative information about the shortcomings of physical fitness of each student (group) and specify the direction of future work.